Bridging the digital divide: Assessing teacher readiness for technology integration in madrasah ibtidaiyah - Dian Hidayati; Nurhikmah Nurhikmah; Riema Afriani Kusumadewi (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
The swift evolution of educational technology has revolutionized learning accessibility, presenting unique challenges and opportunities, especially in remote areas. This study probes the technological readiness of Madrasah Ibtidaiyah (MI) teachers in these marginalized regions, using a quantitative ex post facto research design. A sample of 112 teachers, randomly selected, provided data via Google Forms and questionnaires, analyzed using two-way ANOVA and cluster analysis in SPSS 23. The research aimed to categorize teachers into five technology readiness profiles: explorers, pioneers, skeptics, paranoids, and slow adopters, based on optimism, innovativeness, discomfort, and insecurity. However, findings revealed only three distinct groups: explorers, pioneers, and slow adopters. Explorers showed high technological confidence but limited innovation engagement, while pioneers, despite readiness, faced challenges like scarce resources and insufficient tech knowledge. Slow adopters, largely older teachers, lagged in embracing new technologies. This lag can be attributed to adverse conditions and inadequate infrastructure, preventing full exploitation of digital tools in education. The study highlights the crucial need to overcome these barriers to enhance technology integration in MI schools, thereby improving educational outcomes in underdeveloped areas.